Conventional Banking, Sharia Banking, and Financial Justice - Depid Ismail; Muhammad Noor Sayuti; Diana Farid (Islamicate Institute, 2020)
This article discusses the substantive differences, theoretically, between conventional banking and Islamic banking, which are associated with the formation of financial justice that occurs in the two institutions operating in the two banking systems. This article is written using a qualitative method. The data source is in the form of publication results. This type of data is in narrative empirical documentation, including the narrative of theoretical opinions of previous researchers or reviewers. The data collection technique is done by tracing sources, both print, and online publication sources. The data analysis technique was carried out in a descriptive, interpretive manner and, to some extent, comparative. The results obtained indicate that the financial justice formed in Islamic banking is closer to economic goals.